Good Corporate Governance, Disclosure of Corporate Social Responsibility, Company Size and Company Value (E-Jurnal Akuntansi, 2024)
Company value is the perception of the company's level of success in improving shareholder welfare. A high company value will make the market believe in its current and future prospects. This research aims to examine the influence of GCG, CSR Disclosure, and Company Size on Company Value. This research was conducted on mining companies listed on the IDX in 2018-2020. The sample was determined using a purposive sampling technique which then obtained a sample of 74 samples. The analysis technique used is a multiple linear analysis technique. The results of the analysis of each variable show that the managerial ownership, institutional ownership and company size variables have a positive effect on company value, while the CSR disclosure variable has no significant effect on company value
Keywords: GCG; CSR Disclosure; Company Size; Company Value